Consumption of sugar-sweetened beverages : A cross-sectional study among university students in Sarawak - Cheah, Whye Lian; Law, Leh Shii; Bo, Myat Su; Abigail Eleanor, Gani; Andy Lau, Yueh Lee; Mechyle, Abing; Nur Nadhirah Aisyah, Mohd Yasin (Turkish Society of Public Health Specialists, 2023)
Objective: This study aimed to examine the prevalence and type of Sugar-sweetened Beverages (SSB) consumption among students at a public university in Sarawak. Methods: This was a cross-sectional study conducted among undergraduate students in a public university in Malaysia. Using questionnaires, data on socio-demographics, SSB consumption, family and personal history of diabetes, as well as knowledge of SSB intake was collected. Anthropometry measurement was also taken in the survey. Data were analyzed using IBM SPSS version 22.0. Results: A total of 208 respondents participated in the study. About one-fourth of the respondents consumed SSB at least once daily (83.6%) and as high as 72.1% consumed SSB more than three times a week. The top three most consumed types of SSBs were coffee, flavored milk, and 3-in-1 sachet drink (53.4 to 76.0%). Malay and other ethnic groups (Bumiputra Sarawak, Bumiputra Sabah, Indian, and other ethnic groups) recorded a significantly higher daily consumption of SSB (≥1 time) compared to Chinese respondents. Conclusions: Understanding the pattern of SSB consumption among young adults is important to establish an effective intervention strategy. The findings highlighted the need for targeted interventions aimed at different ethnicities in view of their dietary consumption patterns in a multicultural society like Malaysia.